Pupil dynamics after in-the-bag versus anterior and retropupillary iris-fixated intraocular lens implantation - Sun, Yanxiu; Hammer, Maximilian; Yildirim, Timur Mert; Khoramnia, Ramin; Auffarth, Gerd U. (Scientific reports, 2021)
An Intraocular Lens (IOL) fixated on the iris either anteriorly, as a phakic IOL, or posteriorly, as an aphakic IOL, can influence pupil motility. In this interventional case series study, we evaluated pupil size under different levels of illumination (scotopic = 0.04 lx, low-mesopic = 0.4 lx and high-mesopic = 4 lx) for anterior iris-claw IOL fixation for correcting myopia or hyperopia (IFPH), retropupillary iris-claw IOL fixation to correct aphakia or as treatment for late in-the-bag IOL dislocation/subluxation (IFRP), and capsular-fixation IOL in-the-bag implantation (IB). Pupil size was measured preoperatively for the IFPH- and IB-group as well as 6 months after surgery for all groups. We analyzed a total of 70 eyes: 22 eyes of 11 patients with phakic IOLs, 22 eyes of 20 patients in the IFRP group and 26 eyes of 13 patients in the IB group. Both IFPH and IB showed a smaller postoperative scotopic pupil size, compared with the preoperative values. When compared to postoperative values of IB and IFPH, IFRP showed a significantly smaller postoperative scotopic pupil size (IFPH: 5.89 ± 0.83 mm, IFRP: 4.37 ± 0.83 mm, IB: 5.34 ± 0.98 mm, p < 0.001) while no differences were seen at high-mesopic lighting. Neither of the surgical techniques seems to impair the constriction of the pupil.
Gesehen am 01.12.2021